First, I commend my soul: The testament of Colonel José Teixeira da Silva, new village of northern Extremoz, Captaincy of Rio Grande do Norte (1779) - Nascimento Torres de Paula, Thiago (Em Perspectiva, 2020)
The objective of this research is to present the transcription of the testament of José Teixeira da Silva, Portuguese from the Kingdom, military, Catholic, experienced in the way of the mines, owner of lands, cattle and slaves. The material was made in the Captaincy of Rio Grande do Norte, new village of northern Extremoz, necessarily in the year 1779. The aforementioned´s testament presents itself as an accountability space with celestial and human beings, so the tested person spares no effort to save his soul from the supposed eternal condemnation, or even the torments of purgatory, by distributing the movable and immovable goods with based on earthly affections and strategies. The original document is under the custody of the archive of the Historical and Geographic Institute of Rio Grande do Norte, specifically in the manuscript collection. After all, the transcription on screen carried out according to the rules of the Brazilian State, may serve as a way for the teaching and learning process of young historians and as a source for investigations in the multiple fields of Human and Social Sciences.